Differences in Adolescents' Response Decision and Evaluation for Face-to-Face and Cyber Victimization. (October 2019) - Wright, Michelle F.; Harper, Bridgette D.; Wachs, Sebastian
The current study was designed to assess early adolescents' response evaluation and decision for hypothetical peer victimization vignettes. Participants were 336 (59% girls;X ¯ age = 12.55) seventh and eighth graders from one school in the Midwestern United States. Adolescents read a hypothetical online or offline social situation and answered questions designed to access internal congruence, response evaluation, response efficacy, emotional outcome expectancy, and social outcome expectancy. Girls were more likely to believe that aggressive responses online and offline would lead to positive social and emotional outcome expectancies when compared with boys. Adolescents were more likely to believe that offline and online aggressive responses were legitimate responses to face-to-face victimization, feel that aggressive responses online or offline were easier to execute in response to face-to-face victimization, and that aggressive responses online or offline would lead to positive emotions and better social outcomes.